Nonlinear stochastic relaxation dynamics in spin-crossover solid-state compounds - Gudyma, Iu.V.; Maksymov, A.Iu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
A study of dynamic of spin-crossover solid-state compound has been carried out. The investigated macroscopic phenomenological model for molecular spin-crossover complexes with optical control parameter has been extended to the case of noise action. The noise-driven phase transition was observed. Also, ascertained was the role of additive noise as a main factor for suppressing the potential barrier height.